RATIO OF BROWN RICE FLOUR AND MUNG BEAN FLOUR IN THE MAKING OF SEMPRONG CAKE - Sahid, Emif Rezqia; Lestari, Oke Anandika; Hartanti, Lucky (Universitas Trilogi, 2024)
Semprong is one of Indonesia's signature cookies with a crunchy texture and roll-like shape. The main raw material commonly used in kue semprong is white rice flour. Brown rice is an alternative to rice flour for making kue semprong because its utilization in the food industry sector is still very limited. Rice, which is included in the cereal group, is low in the amino acid lysine, so it would be better if it is paired with other raw materials, such as beans such as green beans. The objective of this study was to obtain the right ratio of brown rice flour and mung bean flour to produce the best abacus cake formulation based on physicochemical and sensory characteristics. Based on the results of the research, the best abacus formulation with the highest score is P3, which is a ratio of 60% brown rice flour and 40% mung bean flour with a moisture content of 3.30%, protein content of 16.80%, ash content of 1.56%, color L* 23.26, color a* 6.62, color b* 7.54, has a yellow color, distinctive aroma of brown rice, crunchy texture, and savory taste.